Case Study: Effect of Giving Boiled Bay Leaf Water to Clients with Hypertension - Aminullah, Muhammad Fasya; Septiany, Maulidya (Media Karya Kesehatan, 2024)
Hypertension is a chronic disease that develops with age and can lead to death. Bay leaf is a non-pharmacological therapy that can lower blood pressure. Bay leaves contain flavonoid compounds that dilate blood vessels and reduce pressure on artery walls, lowering blood pressure to baseline. To provide nursing care through the intervention of administering bay leaf infusion to clients with a nursing diagnosis of the risk of blood pressure instability. Mr. B, 83 years old, complained of stiffness and pain in the neck and back for three days, blurred vision, and a mild headache (P: sudden onset; Q: stabbing pain; R: Pain in the head and shoulders; S: 3 (mild); T: Intermittent). Blood pressure examination revealed 160/100 mmHg. The nursing care results conducted over 7 days with the main intervention of consuming bay leaf infusion twice a day showed successful resolution of the problem, as indicated by the decrease in blood pressure from 160/100 mmHg to 126/80 mmHg. Bay leaves are rich in flavonoids, tannins, and essential oils, proven to be effective in controlling blood pressure and reducing hypertension. This research can only be carried out on patients who do not experience complications from heart or kidney disease by carrying out a TTV examination for each intervention that will be carried out. The results of the evaluation of 14 interventions for 7 days in the form of bay leaf boiled water given in the morning and evening, showed changes in blood pressure levels in Mr. B significantly where Mr. B, which was originally 160/100 mmHg, became 126/80 mmHg.Keywords: Boiled bay leaf water, nursing care, hypertension.